FROM MIDEC TO NEW MIDEC: CAPACITY BUILDING AND THE FUTURE OF INDONESIA-JAPAN AUTOMOTIVE COOPERATION - Hartanto, Hartanto; Amira, Naila Safa (Universitas Prof. Dr. Moestopo (Beragama), 2025)
ABSTRACTThis study analyzes the cooperation between Indonesia and Japan through the New Manufacturing Industry Development Center (New MIDEC) program in strengthening the capacity of Indonesia’s automotive industry during the 2019–2024 period. As a continuation of the previous MIDEC under the Indonesia–Japan Economic Partnership Agreement (IJEPA), the program aims to enhance the competitiveness of the national automotive sector through human resource development, technology transfer, and industrial strengthening. Employing a descriptive qualitative method, data were collected through document analysis and in-depth interviews with officials from the Ministry of Industry. The findings reveal that New MIDEC has made a significant contribution to human resource capacity building, particularly through modular training and the empowerment of small and medium-sized enterprises (SMEs). Nevertheless, its implementation continues to face challenges, including technological gaps and limited adoption of advanced technologies by domestic industries. Accordingly, this study recommends strengthening cross-sectoral collaboration and optimizing technology transfer to ensure that New MIDEC delivers greater benefits for the development and global competitiveness of Indonesia’s automotive industry.Keywords: New MIDEC, IJEPA, Capacity Building, Automotive IndustryABSTRAKPenelitian ini menganalisis kerja sama Indonesia–Jepang melalui program New Manufacturing Industry Development Center (New MIDEC) dalam upaya penguatan kapasitas industri otomotif Indonesia pada periode 2019–2024. Program ini merupakan kelanjutan dari MIDEC sebelumnya yang menjadi bagian dari Indonesia–Japan Economic Partnership Agreement (IJEPA), dengan tujuan meningkatkan daya saing industri otomotif nasional melalui pengembangan sumber daya manusia, transfer teknologi, dan penguatan sektor terkait. Penelitian menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data berupa studi dokumen dan wawancara mendalam dengan Kementerian Perindustrian. Hasil penelitian menunjukkan bahwa New MIDEC berkontribusi signifikan terhadap peningkatan kapasitas sumber daya manusia, terutama melalui pelatihan modular dan penguatan industri kecil dan menengah (IKM). Meski demikian, implementasinya masih menghadapi sejumlah kendala, antara lain kesenjangan teknologi dan rendahnya tingkat adopsi teknologi oleh industri domestik. Oleh karena itu, penelitian ini merekomendasikan penguatan kolaborasi lintas sektor serta optimalisasi alih teknologi agar New MIDEC dapat memberikan manfaat lebih besar bagi pengembangan daya saing industri otomotif Indonesia di tingkat global.Kata kunci: New MIDEC, IJEPA, Capacity Building, Industri Otomotif